Using the Judgment Bias Task to Identify Behavioral Indicators of Affective State: Do Eye Wrinkles in Horses Reflect Mood? - Hintze, Sara; Schanz, Lisa (Frontiers in Veterinary Science, 2021)
Identifying and validating behavioural indicators of mood is important for the assessment of animal welfare. Here we investigated whether horses’ eye wrinkle expression in a presumably neutral situation is a measure of mood as assessed in a cognitive Judgement Bias Task (JBT). To this end, we scored pictures of the left and right eye of 16 stallions for different aspects of eye wrinkle expression and tested the same individuals on a spatial JBT with active trial initiation. Eye wrinkle expressions was assessed by a qualitative assessment, i.e. the overall assessment of how “worried” horses look, the number of wrinkles and the angle measured at the intersection of lines drawn through the eyeball and the topmost wrinkle. Correlations between the three eye wrinkle measures and the optimism index as a measure of horses’ decisions in the JBT were not statistically significant, but with increasing optimism index horses tended to be scored as looking less worried (qualitative assessment). We discuss our findings from different perspectives and make suggestions for future research, e.g. by calling for experimental induction of mood and thus greater variation within and/or between individuals and by investigating the interplay between shorter-lasting emotional and longer-lasting mood states to further explore the potential use of the JBT to validate eye wrinkles and other facial or body expressions as indicators of mood.